Preventive Effect of Exercise on Kidney Fibrotic Pathway in Hypertension - Afifah, Farabillah; Dewi Irawati Soeria Santoso (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Uncontrolled hypertension can progress to kidney damage characterized by structural and functional changes, ultimately contributing to kidney fibrosis. Although, hypertension can be treated. However, the prevalence of hypertension in Indonesia is increasing. Therefore, proper treatment is necessary. Elevated levels of Transforming Growth Factor-Î²1 and Connective Tissue Growth Factor are critical factors that are key drivers of fibrogenic pathway. Appropriate exercise can control blood pressure, renal function, and prevent kidney fibrosis due to hypertension by activating the nitric oxide signaling pathway and reducing the regulation of the TGF-Î², p-Smad2/3 and CTGF. This study aims to determine the optimal type of exercise to prevent kidney fibrosis caused by hypertension. Articles used are limited to the publication year between 2018 and 2024. We analyzed the role of exercise on kidney fibrotic pathway in hypertension using PRISMA methods from PubMed, ScienceDirect, Scopus, and Google Scholar. We found 7 articles and proved several significant effects of exercise on hypertension subjects. This study summarized that moderate-intensity exercise is more influential in controlling blood pressure and renal function, as well as inhibits kidney fibrosis due to hypertension.